2012
DOI: 10.1080/11263504.2012.727882
|View full text |Cite
|
Sign up to set email alerts
|

Determination of genetic variation and relationship in Thymus vulgaris populations in Syria by random RAPD markers

Abstract: In order to detect the genetic variation and relationship among Thymus vulgaris populations collected from five different provinces in Syria, Random Amplified Polymorphic DNA (RAPD) analysis was applied. A total of 198 bands were obtained using 27 primers. Polymorphism was 90.91% while the polymorphism of the total bands was 78.73%, which indicated a close relationship among some populations. Populations of T. vulgaris were characterized by 37 unique bands of which eight were negative. Dendrogram based on Perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
4
2
0
Order By: Relevance
“…Our results were entirely compatible with results on five Palestinian Thymus species, T. kotschyanus, T. caespititius, [28,29,38]. In addition, numerous research studies on Thymus species from several countries showed that the rate of polymorphism ranges from 62% to 92% [39,40,[41][42][43]. Nevertheless, the polymorphism level obtained in this study is rather lower than the recorded average polymorphism (94.31 percent) [30], which examined genetic polymorphism in 13 Thymus accessions collected from different habitats in Iran using 20 RAPD primers.…”
Section: Polymorphism Revealed By Rapd and Issr Primerssupporting
confidence: 90%
“…Our results were entirely compatible with results on five Palestinian Thymus species, T. kotschyanus, T. caespititius, [28,29,38]. In addition, numerous research studies on Thymus species from several countries showed that the rate of polymorphism ranges from 62% to 92% [39,40,[41][42][43]. Nevertheless, the polymorphism level obtained in this study is rather lower than the recorded average polymorphism (94.31 percent) [30], which examined genetic polymorphism in 13 Thymus accessions collected from different habitats in Iran using 20 RAPD primers.…”
Section: Polymorphism Revealed By Rapd and Issr Primerssupporting
confidence: 90%
“…Five of thyme species were identified and subjected to RAPD as the simplest molecular markers that able to recognize the genetic relationships among them. Nearly 78.6% of the bands were found as DNA polymorphic, confirmed the results obtained from different research studies from different countries on thymes species with reported polymorphism percentage varies from 62-92% (Bagherzadeh, 2009;Alamdary et al, 2011;Ben el Hadj Ali et al, 2012;Pluhár et al, 2012;and Khalil et al, 2012). Using three of universal primers ((OPD-19, OPH-02 and OPAN-08) out of eight were found to generate relatively high level of DNA polymorphism among five thyme species (78.6%) in this study.…”
Section: Discussionsupporting
confidence: 78%
“…The same was obtained in other RAPD analysis of Thymus species growing in eastern Anatolia region of Turkey, using primers OPA-2, OPH-16, and OPH-18 with totally 8 polymorphic bands were produced (Sunar et al, 2009). In Syria, a research study for determination of genetic variation among Thymus vulgaris populations by RAPD markers, almost 27 primers were used which were able to produce 198 total bands, with a mean of 7.3 bands for each primer (Khalil et al, 2012). The mean score of 12.7 bands, obtained using the three primers in this research study was good enough to reveal the genetic relationships among the selected Thymes species' subjected to RAPD tests, compared with previous studies.…”
Section: Discussionsupporting
confidence: 54%
“…These data indicated that the composition of the essential oil is regulated by a number of genes that are extensively distributed throughout the plant genome [1,29,30]. Khalil et al [31] used RAPD analysis to determine the genetic relationship between T. vulgaris populations collected in Syria. In their study, 13 individuals were analyzed using 27 primers, which generated 180 polymorphic bands from 198 bands.…”
Section: Discussionmentioning
confidence: 99%